The Library as Strategic Investment: Results of the Illinois Return on Investment Study - Kaufman, Paula T. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
University administrators are asking library directors to demonstrate their library’s value to the institution in easily articulated quantitative terms that focus on outputs rather than on traditionally reported input measures. This paper reports on a study undertaken at the University of Illinois at Urbana-Champaign that sought to measure the return on the university’s investment in its library. The study sought to develop a quantitative measure that recognizes the library’s value in supporting the university’s strategic goals, using grant income generated by faculty using library materials. It also sought to confirm the benefits of using electronic resources and the resulting impact on productivity over a 10-year period. The results of this study, which is believed to be the first of its kind, represent only one piece of the answer to the challenge of representing the university’s total return from its investment in its library.